John Magee papers - Magee, John, 1922-1941.; Magee, John, 1922-1941.; Magee, John, 1922-1941.
Manuscript poems entitled, "High Flight" and "Per Ardua," written by Magee while serving as a pilot with the Royal Canadian Air Force in England during World War II; two photographs of Magee (undated); and two newspaper clippings (1946, undated).
Photocopies and digital scan, in part.
Aviator and poet; full name: John Gillespie Magee, Jr.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Canada. -- Royal Canadian Air Force; Flight; World War, 1939-1945 -- Poetry; World War, 1939-1945 -- England; Aviators; Poets